Field study of complements to supervisory leadership in more and less flexible work settings - Terri L. Griffith; Emma S. Nordbäck; John E. Sawyer; Ronald E. Rice (Journal of Organization Design, 2018)
Self-management is increasingly required by people in jobs with flexible schedules and locations, freelance arrangements, and other forms of organizational job design. Successful self-management requires a sense of engagement with one's work. We build from the substitutes for leadership literature to develop a model of work design focused on how complements to supervisory leadership foster work engagement. The model illustrates a parsimonious set of possible complements to supervisory leadership: feedback from the work itself, technology support of work, knowledge to work independently, electronic communication with supervisors, and alternative workplace use as predictors of work engagement. Results are from a two-period field study of a Nordic telecom company experienced with flexible work practices. Additionally, in time 2, we compare the data from this first organization with a Nordic transportation company that is less experienced with flexible work practices. Our results show the strongest relationships with work engagement are feedback from the work itself and technology support of work. Supervisor electronic communication also plays a role in work engagement, mediated by alternative workplace use. We highlight shifts in work design that can enable more flexible work settings while maintaining worker engagement in our increasingly digital organizations.
Keywords: 650; Complements to supervisory leadership; Digital organizations; Engagement; Feedback; Flexible work; Substitutes for leadership; Telecommuting; Work design